Complete solutions manual for Multivariable calculus, fifth edition - Clegg, Dan (Thomson/Brooks/Cole, 2003)
Contains detailed solutions to all exercises in the texts Multivariable calculus, 6th ed. and Multivariable calculus : early transcendentals, 6th ed. (chapters 11-18 of Calculus, 6th ed. and chapters 10-17 of Calculus : early transcendentals, 6th ed.)